(untitled) (Indian Journal of Animal Production and Management, 2014)
Present study was conducted to compare cervical mucus characteristics viz.Quantity, appearance, spinnbarkeit value and consistency, between natural and induced estrus crossbred cows. It was observed that naturally exhibited and induced cow there is markdifference between discharges of cervical mucus membrane. Quantity is copious in about 60&54% in natural and induced cow respectively and cervical mucus discharge at the time of A.I.was clear in 73% and 61% of animals in natural and induced estrus, respectively.Maximum number of animals in both natural and induced estrus (75% & 79%, respectively) showed spinnbarkeit value of cervical mucusin the range of 0-8cm, followed by 8-16, 16-24 and >24cm. Consistency in estrus period for most of the natural and induced estrus animals (56% and 53%, respectively) showed thin mucus consistency followed by moderate and thick consistency.